Antes e depois da cirurgia bariátrica: dispositivos biopolíticos, blogs terapêuticos e outras narrativas biomidiáticas - Deyvisson Pereira da Costa (2014)
The increasing interest for care with the body in order to keep it healthy is easily noticed in the contemporary society transforming therapies into a survey to the modes of subjectivation.When considered the technologies for obesity control, we can see the attention is unfolded. This research aims to describe how a net of techniques, discourses and biomedical and communicational technologies engender biopolitical devices in therapeutic courses, specifically as blog associate themselves to gastroplasty, also known as bariatric surgery or stomach reduction, building heterogeneous devices for corporal weight loss. It is questioned how the bariatric patients blogs store, answer and perhaps reinvent the biopolitical discourses. Eleven narratives were selected among those read and recommended by an author identified in exploratory research. From the verbal, non-verbal and interactional elements used by this group of women, the senses they attribute to the surgery and to obesity, the process of selfwriting and exposure and the net mediation are described here considered biosociabilties. The biomedical discourses are present in blogs and contribute to meaning production, especially while participant of rhetoric of risk.In complement to the accountability of the individual under the imperative of autonomy, the risk is extended from corporal care to the several scopes in articulation with the state-owned, media and entrepreneurial discourses. Thus, the self-writing itself can become a resource to the exposure of performances in the corporal adequacy as a result of the sanitary made correct choices of the risk management. But some ambiguities related to the themes, tactics, visibilities and sociabilities are also identified among the processes of subjectivity added by the biopolitical and therapeutic devices.